2002
DOI: 10.1248/cpb.50.298
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2,2'-Dihydroxybisphenols and Antiviral Activity of Some Bisphenol Derivatives.

Abstract: Triphenylmethane-type bisphenols have antioxidant activity, 1,2) and some of the derivatives show anticancer activity.3)Recently, we reported a conventional procedure for the preparation of triphenylmethane-type 2,2Ј-dihydroxybisphenols. 4) For the synthetic application of the procedure and biological evaluation of the related compounds, we attempted to synthesize diphenylmethane-type 2,2Ј-dihydroxybisphenol derivatives with some aliphatic aldehydes as starting material. In this paper, we wish to report the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 6 publications
2
12
0
Order By: Relevance
“…15) described in our previous paper. 1,2) In structural comparison of 3a to 3d, the introduction of two methoxy groups into a phenyl ring resulted in a slight reduction of the anti-HSV-1 activity, as well as decreased cytotoxicity. We also observed that the modification of 2,2Ј-dihydroxytriphenylmethane derivatives 4b to 4c, in which a phenyl ring is substituted to a pyridine ring, increases its activity and decreases its cytotoxicity.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…15) described in our previous paper. 1,2) In structural comparison of 3a to 3d, the introduction of two methoxy groups into a phenyl ring resulted in a slight reduction of the anti-HSV-1 activity, as well as decreased cytotoxicity. We also observed that the modification of 2,2Ј-dihydroxytriphenylmethane derivatives 4b to 4c, in which a phenyl ring is substituted to a pyridine ring, increases its activity and decreases its cytotoxicity.…”
Section: )mentioning
confidence: 99%
“…3) Antiviral Activity Assay The antiviral activities of the compounds were measured by the plaque reduction assay 8) described in previous paper. 1,2) Calculated EC 50 values for the tested compounds are summarized in Table 4. Cytotoxicity Assay The antiviral activities of the compounds were examined as described below.…”
Section: 4-dihydroxy-3؆4؆-methylenedioxytriphenylmethane (3b) [Metmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are a great many combinations of starting phenols and aromatic aldehydes to provide a considerable number of target compounds. Considering the results described in this paper, together with the information in our previous report on 2,2Ј-dihydroxytriphenylmethanes, 2) further study is warranted.…”
Section: Resultsmentioning
confidence: 75%
“…Using TFA as the catalyst for the preparation of the target compounds is conventional and usually gives good to moderate results. 6) The physical data for compounds (1)(2)(3) are summarized in Table 2. NMR-spectroscopic analyses confirmed the symmetrical structure of the target compounds (1b, 2a-d) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%